(untitled) (Docentes 2.0 Journal, 2013)
The legal professional must be a person forged in the furnaces of Multidisciplinarity, because it is necessary that the lawyer is an integral person capable of addressing any situation of daily life and frame it in the extensive framework that constitutes the legal system, to resolve situations Administrative and legal. Now, one of those important subjects in the academic training of a lawyer is Criminology. The criminological knowledge broadens the vision of the function of the law, which is not merely to punish those who have infringed at all costs, and provides an image of the criminal closest to reality, which allows him to verify that the antisocial is a being concrete, flesh and blood, that feels and suffers, and is subject to emotions and needs and that generates, works under the empire of circumstances that embrace it.